Aircraft engine design - Mattingly, Jack D. (American Institute of Aeronautics and Astronautics, 2002)
Annotation A design textbook attempting to bridge the gap between traditional academic textbooks, which emphasize individual concepts and principles; and design handbooks, which provide collections of known solutions. The airbreathing gas turbine engine is the example used to teach principles and methods. The first edition appeared in 1987. The disk contains supplemental material. Annotation c. Book News, Inc., Portland, OR (booknews.com).
Keywords: Aircraft gas-turbines -- Design and construction.; elektronické knihy; electronic books